Application Of the Expository Learning Method In Understanding The Perception Of Hijaiyah Letter Forms In 'Mild Mentally Retarded' Students at SLB YPLB-LB Hegar Asih Cipaganti Bandung - Zul Andrivat; Aan Hasanah; Badrudin Badrudin; Dewi Sadiah (MASI Mandiri Edukasi, 2026)
This study was motivated by students with mild intellectual disabilities' limited ability in recognize and understand the shapes of Hijaiyah letters at SLB YPLB-LB Hegar Asih Cipaganti Bandung. These difficulties were related to limitations in visual perception and the lack of learning methods suited to students’ characteristics and needs. The study aimed to examine the application of the Expository Learning method in improving students’ understanding of Hijaiyah letter forms in Islamic religious education. This research employed a qualitative case study approach involving a small group of students with mild intellectual disabilities. Data were collected through classroom observations, teacher interviews, and documentation of learning activities. The findings showed that the Expository Learning method positively supported students’ ability to recognize, name, and write Hijaiyah letters more accurately than before its implementation. Improvements were observed qualitatively through increased student focus, more active teacher-student interaction, and students’ ability to distinguish letter shapes step by step during learning activities. The use of visual media, structured explanations, and repetition exercises helped students better understand and memorize Hijaiyah letters. Overall, the method created a more organized and meaningful learning process for students with mild intellectual disabilities.